Desain dan Analisis Distribusi Suhu pada Mesin Pengering Cabai Berbahan Bakar LPG (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to analyze the temperature distribution in an LPG-fueled chili drying machine using Computational Fluid Dynamics (CFD) simulation. The simulation was performed using SolidWorks Flow Simulation 2022 to investigate the effect of inlet air temperature and velocity on temperature uniformity inside the drying chamber. Three inlet temperature variations were applied: 60°C, 70°C, and 80°C, combined with two air velocities of 10 m/s and 11 m/s. The results showed that these parameters significantly influence temperature distribution. The optimum condition was achieved at 70°C and 10 m/s with a temperature uniformity efficiency (